Antidepressant-Like Effects of Gyejibokryeong-hwan in a Mouse Model of Reserpine-Induced Depression - Park, Bo-Kyung (Biomed Res Int, 2018)
Treatment with the antihypertensive agent reserpine depletes monoamine levels, resulting in depression. In the present study, we evaluated the antidepressant effects of Gyejibokryeong-hwan (GBH), a traditional Korean medicine, in a mouse model of reserpine-induced depression. Mice were treated with reserpine (0.5 mg·kg(−1), i.p.) or phosphate-buffered saline (PBS, i.p., normal) once daily for 10 days. GBH (50, 100, 300, and 500 mg·kg(−1)), PBS (normal, control), fluoxetine (FXT, 20 mg·kg(−1)), or amitriptyline (AMT, 30 mg·kg(−1)) was administered orally 1 h prior to reserpine treatment. Mouse behavior was examined in the forced swim test (FST), tail suspension test (TST), and open-field test (OFT) following completion of the treatment protocol. Administration of GBH reduced immobility time in the FST and TST and significantly increased the total distance traveled in the OFT. Plasma serotonin levels were significantly lower in control mice than in normal mice, although these decreases were significantly attenuated to a similar extent by treatment with GBH, FXT, or AMT. Reserpine-induced increases in plasma corticosterone were also attenuated by GBH treatment. Moreover, GBH attenuated reserpine-induced increases in interleukin- (IL-) 1β, IL-6, and tumor necrosis factor- (TNF-) α mRNA expression in the hippocampus. In addition, GBH mice exhibited increased levels of brain-derived neurotrophic factor (BDNF) and a higher ratio of phosphorylated cAMP response element-binding protein (p-CREB) to CREB (p-CREB/CREB) in the hippocampus. Our results indicated that GBH can ameliorate depressive-like behaviors, affect the concentration of mood-related hormones, and help to regulate immune/endocrine dysfunction in mice with reserpine-induced depression, likely via activation of the BDNF-CREB pathway. Taken together, these findings indicate that GBH may be effective in treating patients with depression.